2006
DOI: 10.1016/j.febslet.2006.11.029
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding site in the plant ADP‐glucose pyrophosphorylase large subunit

Abstract: The ATP binding region in the catalytically inactive large subunit (LS) of the potato tuber ADP-glucose pyrophosphorylase was identified and investigated. Mutations at the ATP binding significantly affected not only the apparent affinities for ATP and Glc-1-P, and catalytic rate but also in many instances, sensitivity to 3-phosphoglycerate. The catalytic rates of the LS mutant enzymes correlated most strongly with changes in the affinity toward ATP, a relationship substantiated by photoaffinity labeling studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…The large subunit, then, can accumulate more nondeleterious nonsynonymous mutations for AGPase activity than can the small subunit. However, the roles of each AGPase subunit in enzyme function are not clear, since each subunit has activity when expressed alone in E. coli (Iglesias et al, 1993;Burger et al, 2003), and mutations in either subunit affect both catalytic and allosteric properties (Hannah and Nelson, 1976;Cross et al, 2004Cross et al, , 2005Hwang et al, 2006Hwang et al, , 2007. It should also be noted that the regulatory subunits of the Archaeal type H þ -ATPase and vacuolar type H þ -ATPase evolved at a slower rate compared with the catalytic subunits (Marin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The large subunit, then, can accumulate more nondeleterious nonsynonymous mutations for AGPase activity than can the small subunit. However, the roles of each AGPase subunit in enzyme function are not clear, since each subunit has activity when expressed alone in E. coli (Iglesias et al, 1993;Burger et al, 2003), and mutations in either subunit affect both catalytic and allosteric properties (Hannah and Nelson, 1976;Cross et al, 2004Cross et al, , 2005Hwang et al, 2006Hwang et al, , 2007. It should also be noted that the regulatory subunits of the Archaeal type H þ -ATPase and vacuolar type H þ -ATPase evolved at a slower rate compared with the catalytic subunits (Marin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been used in attempts to reveal the role of the two AGPase subunit types in higher plants. Numerous studies using various genetic, mutagenic, and biochemical strategies have strongly suggested that the SS has both catalytic and regulatory activities, and that the LS is mainly responsible for modulating the allosteric regulatory properties of the SS in the heterotetrameric enzyme (Ballicora et al 1995;Salamone et al 2000;Frueauf et al 2003;Hwang et al 2006). Although the LS is usually non-catalytic, recent studies have demonstrated that recombinant LSs (mutated or natural) show defective catalytic activity, both alone and in the presence of the SS in vitro Ventriglia et al 2008;Hwang et al 2008;Petreikov et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Even when the L subunit is not catalytic, it binds substrate and activator molecules. This may contribute to the synergistic effect seen when the L subunit influences the properties of the S subunit and vice versa (7)(8)(9).…”
mentioning
confidence: 99%